(untitled) (Orfeu, 2024)
The study of the vertical or harmonic dimension of music involves two fundamental perspectives: the lexical and the syntactic. In the lexical context, we deal with chords, while in the syntactic perspective, we focus on the relationships between these chords. When we approach the harmonic lexicon, we encounter two fundamental dimensions, one of a quantitative nature and the other qualitative. The quantitative dimension concerns the counting of the notes that compose the chords, i.e., their cardinality. Meanwhile, in the qualitative realm, we adopt the expression ’degree of dissonance’ to describe this characteristic. In the first part of this study, we will explore the construction of a harmonic lexicon with chords containing three notes, using combinations of intervals between the different notes of the chromatic scale. In the second part, we will analyze various factors of a syntactic nature, including tonality, parsimony, degree of dissonance, stochastic aspects, and the concept of intertextuality in music.